1987
DOI: 10.1002/macp.1987.021880706
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of biaxial nematic side chain polymers with laterally attached mesogenic groups

Abstract: The synthesis and characterization of liquid crystalline side chain polymers with mesogenic groups laterally attached to the polymer main chain are described. By variation of the terminal group, mesogenic moiety or spacer length, a change in the glass transition temperature, the nematic to isotropic transformation temperature and the stability of the nematic phase can be achieved. With increasing length of terminal groups, a distinct odd-even effect of the nematic to isotropic phase transformation temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(44 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…The comparison among the thermal behavior of the dendrimers reported here and the linear side chain polymers (derived polymethacrylate and polysiloxane), synthesized by Finkelmann group is especially relevant. In Table are collected data of the mesomorphic properties of two representative side chain polymers (SCP) bearing laterally attached mesogenic units similar to L1(C4) and L2(C5) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison among the thermal behavior of the dendrimers reported here and the linear side chain polymers (derived polymethacrylate and polysiloxane), synthesized by Finkelmann group is especially relevant. In Table are collected data of the mesomorphic properties of two representative side chain polymers (SCP) bearing laterally attached mesogenic units similar to L1(C4) and L2(C5) .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we used an approach similar to that employed in side chain liquid crystalline polymers. In these polymeric systems, it has been shown that the introduction of laterally attached mesogenic units makes it difficult for the units to adopt the side‐by‐side molecular arrangement typical of lamellar phases, thus favoring a biaxial nematic order …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCEs can be prepared via side chain, main chain or combined main chain/side group liquid crystalline polymers27~39) using one step or two steps procedure. One step preparations were carried out by radical copolymerization of [31][32][33].…”
Section: Liquid Crystalline Elastomers: Synthesismentioning
confidence: 99%
“…On the other hand one is forced to conclude on the basis of the sign and the magnitude of the electrooptical response that it is the reorientation of the long axis of the mesogenic unit which contributes predominantly to the electrooptical response. It thus seems that constraints exist in the polymers considered here not only for motions about the long axis [17][18][19]-which gives rise to a biaxial character of the nematic phase-but also for reorientational motions of the long axis itself. These constraints prevent a free rotation of the mesogenic units about the short axis and force the long axis to reorient only along selected paths.…”
Section: Theoretical Analysis Of the Relation Between Electrooptical mentioning
confidence: 99%